Researching the digital economy and the creative economy: Free gaming shards and commercialised making at the intersection of digitality and creativity. (June 2023) - Jordan, Tim; Richterich, Annika
Despite the creative economy relying on digital technology and the digital economy needing creative input, policy and research alike tend to miss or underestimate interdependencies between these two economies. This article argues for the importance of acknowledging interdependencies and overlaps between the cultural and creative economy and the digital economy – while likewise refraining from implicitly conflating the two. Starting from a comparative literature review that identifies key features of creative economy and digital economy literature and the few detailed works on overlaps, it elaborates on this argument by examining two case studies. In discussing and comparing digital games and do-it-yourself electronics e-commerce, this article illustrates overlaps of practices relevant to both, digital and creative economy, and elaborates on why it matters to acknowledge interdependencies rather than merging the two.